SUCCESSFUL TREATMENT WITH SPINAL NEUROSTIMULATION OF INTRACTABLE NEUROPATHIC CHRONIC PAIN IN PATIENTS WITH DEPRESSION: A SERIES OF 60 CASES - Marcela Nour; Ana-Maria Ciubara; Anca Sava; Alin Constantin Iordache; Ana-Maria Dumitrescu; Ion Poeată (Romanian Society of Oral Rehabilitation, 2024)
Background Patients with chronic neuropathic pain often report symptoms of depression. The aim of this work is to determine the intensity of chronic neuropathic pain and to identify the efficacy of spinal neurostimulation in a group of patients with spinal surgery and depression. Materials and Methods: The study includes 60 patients with chronic neuropathic pain after spinal surgery, who received spinal cord neurostimulation implant between October 2017 and January 2024, at the Professor Nicolae Oblu Emergency Clinical Hospital, Iasi. Prior to the spinal implant, the patient was evaluated neurologically, psychologically, imaging, electromyography and underwent appropriate treatment for chronic neuropathic pain for about 3 months. The patient self-assessed himself by completing the VAS pain scale, as well as the Roland Morris scale. Results: Analysis of the data indicated that 37 women (61.7 %) and 23 men (38.3 %) were included, with an average age of 53.87 ± 12.033 years, the majority (35 patients, 58.3 %) being from urban areas. 39 cases (65 %), mainly women (29 patients, 78.4 %) presented depressive syndrome. In 26 cases (43.3%) chronic neuropathic pain started one year after surgery. Neurosurgical interventions prior to chronic neuropathic pain were mainly herniated disc (53 cases, 88.33%). The pain onset was generally quite violent, with 55 patients (91.7%) experiencing pain intensity between 7 and 10 on the VAS scale. The situation improved statistically significantly after implantation, with patients' VAS pain, this time, ranging from 1 to 8. Only in patients with depressive syndrome was there a statistically significant (p = 0.041*) decrease (3.21 ±2.002 versus 4.05 ± 2.012) in the average VAS pain score after implant compared to patients without depressive syndrome. Conclusion: Neurostimulation is effective long-term as an adjuvant treatment for chronic neuropathic pain in patients with depressive syndrome.